COMPARATIVE ANALYSIS OF TOWER BASE TRANSCEIVER STATION (BTS) FOOT 4 BETWEEN BRACING TYPE V WITH BRACING TYPE X - Sumaidi (CI-TECH, 2021)
The development of an area must be followed by the development of adequate facilities and infrastructure to support the activities of that area. Therefore, an effective and efficient transportation service is needed. The bridge is a means of transportation that functions to connect roads that have been cut off due to obstacles either natural or man-made. The existence of the bridge is expected to facilitate and speed up the trip. The Brantas Bridge that connects Sukoanyar and Krembung Villages uses the warren bridge type, in this analysis a modification is made using a parking type bridge. The modification of the bridge shows that the warren type has a displacement joint of 0.80 cm with a total weight of 2861.475 kN while the parker type has a displacement joint of 29.34 cm with a total weight of 3190.945 kN. In this research, the modified type of warren is suitable for use because it is stronger and more economical than the type of parker.